THE POST M&A OPERATING PERFORMANCE OF NORDIC ACQUIRERS - Toljander, Teemu (My University, 2015)
The increase of worldwide M&A transactions in recent decades has been followed by substantial increase of M&A activity in the Nordic countries. The purpose of this study is to examine causality between Nordic acquirers and post-acquisition operating performance. The second purpose of this study is to investigate do different deal determinants have effect on acquirers post-acquisition operating performance. Unlike previous studies this study also examines the effect of intra-Nordic deal and the recent financial crisis on operating performance of acquirers. The sample consists of 102 deals made by Nordic acquirer. Accounting data are collected one year prior and two years following the M&A, whereas data of deal determinants are collected deal by deal. Four different measures are used to determine operating performance. Moreover change model and intercept model are applied to determine significance between pre-acquisition and post-acquisition operating performance. The results point out that there exist only slight evidence about Nordic acquirers’ operating performance improvements. Moreover the results imply that acquirers’ pre-acquisition performance is significant explaining factor for the acquirers’ post-acquisition performance. According to findings deal determinants as acquirer’s pre-acquisition leverage, takeover strategy and relative size of target have a matter when acquirers’ post-acquisition operating performance is considered. Finally findings report some evidence about intra-Nordic acquirers’ operating performance improvements. In conclusion to some extent Nordic acquirers seem to have gained acquisition-induced synergy advantages. Moreover this study provides evidence that different deal determinants have a matter in terms of acquirer’s post-acquisition operating performance. Finally the recent financial crisis does not seem to have at least negative effect on Nordic acquirers’ operating performance.
Keywords: M&A; Nordic acquirer; operating performance; deal determinants; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|